Efficacy of Thiamine in the Treatment of Postcardiac Arrest Patients: A Randomized Controlled Study - Suntornwit Pradita-ukrit; Veerapong Vattanavanit (Critical Care Research and Practice)
Background. Thiamine administration has been shown to improve survival in a postcardiac arrest animal study. We aimed to evaluate the efficacy of thiamine in comatose out-of-hospital cardiac arrest (OHCA) patients following return of spontaneous circulation. Methods. A randomized, double-blinded, placebo-controlled study was conducted. Thirty-seven OHCA patients were randomly assigned to receive either thiamine 100 mg every 8 hours or a placebo. The primary outcome was 28-day all-cause mortality. Results. Over the course of 2 years, 37 patients were randomized to either receive thiamine (n = 20) or a placebo (n = 17). The primary outcome was not different between the groups: 10/20 (50%) in the thiamine group vs. 8/17 (47.1%) in the placebo group (P=0.93 by the log-rank test). There were no significant differences in secondary outcomes between the groups (good neurological outcome, lactate level, and S100B level). Conclusions. In this study, there were no significant differences in survival outcome. Further studies with a larger population are necessary to confirm these results.